In Vitro Radiosensitization of Esophageal Cancer Cells with the Aminopeptidase Inhibitor CHR-2797 - Anbalagan, Selvakumar; Biasoli, Deborah; Leszczynska, Katarzyna B.; Mukherjee, Somnath; Hammond, Ester M. (Radiation research, 2015)
With the increased incidence of esophageal cancer, chemoradiotherapy continues to play an important role in the management of this disease. Developing potent radiosensitizers is therefore critical for improving outcomes. The use of drugs that have already undergone clinical testing is an appealing approach once the side effects and tolerated doses are established. Here, we demonstrate that the aminopeptidase inhibitor, CHR-2797/tosedostat, increases the radiosensitivity of esophageal cancer cell lines (FLO-1 and OE21) in vitro in both normoxic and physiologically relevant low oxygen conditions. To our knowledge, the effective combination of CHR-2797 with radiation exposure has not been reported previously in any cancer cell type. The mechanism of increased radiosensitivity was not dependent on the induction of DNA damage or DNA repair kinetics. Our data support the need for further preclinical testing of CHR-2797 in combination with radiotherapy for the treatment of esophageal cancer.